Carbon dot and BiVO4 quantum dot composites for overall water splitting via a two-electron pathway. Issue 39 (27th September 2016) - Wu, Xiuqin; Zhao, Juan; Guo, Sijie; Wang, Liping; Shi, Weilong; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract : Carbon dot and BiVO4 quantum dot composites (CDs/BiVO4 QDs) show a significantly improved photocatalytic activity and high stability for overall water splitting. Abstract : Carbon dot and BiVO4 quantum dot composites (CDs/BiVO4 QDs) show a significantly improved photocatalytic activity and high stability for overall water splitting. By using 5% CDs/BiVO4 QDs as photocatalysts, the H2 evolution of 0.92 μmol h −1, was achieved under solar light irradiation without any cocatalysts or sacrificial reagents, which is about 4 times that of BiVO4 QDs (0.21 μmol h −1 ). Note that, for the CD/BiVO4 QD catalyst, the produced H2 and O2 are approximately equal to the stoichiometric ratio (H2  : O2 = 1.80 : 1), while that of BiVO4 QDs is nonstoichiometric (about only 0.06 : 1). In addition, the present water splitting occurs via a two-electron pathway and CDs and BiVO4 QDs served as the reduction and oxidation reaction active sites, respectively.